Evaluation of the Retro-Orbital Fatty Tissue Volume in Delayed Orbital Blow-Out Fractures. Issue 3 (May 2016) - Pilanci, Ozgur; Ceran, Fatih; Sagir, Mehmet; Teken, Abdurezzak; Kuvat, Samet Vasfi
Abstract : Purpose: In patients where diplopia and enophthalmia are manifest, surgical intervention is usually necessary. The pathogenesis of these symptoms usually includes the prolapse of orbital tissues into the sinus or compression by the surrounding bone structures. Although the retro-orbital fatty tissue, orbital fascia, and the muscle tissue can be reduced to the original place after being incarcerated into the maxillary space, it is obvious that the procedure can lead to significant fibrosis in these structures. The authors have aimed to carry out a quantitative evaluation of the fatty tissue volumes in patients with repair delayed for more than two weeks. Methods: The preoperative and postoperative fatty tissue volumes and the changes in total orbital volume were evaluated by using CT on the patients (n = 9) who were consulted to the authors' clinic from other health centers. Results: Although no significant correlation was observed between the prolapsed volume and the postoperative reduction in the fatty tissue, the reduction in the retro-orbital fatty tissue was statistically significant. Conclusion: Evaluating postoperative retro-orbital fatty tissue volumes may have implications for surgical intervention in the future. Abstract : Quantitatively describing the reduction in the volume of the fatty tissue may shed light to the planning of secondary procedures to correct fatty tissue volume loss following fractures of the orbital floor.